Oxidative Stress Marker Aberrations in Multiple Sclerosis: A Meta-Analysis Study - Zhang, Shu-Yao; Gui, Lue-Ning; Liu, Yi-Ying; Shi, Sha; Cheng, Yong (Frontiers in Neuroscience, 2020)
Oxidative stress has been suggested to play a key role in multiple sclerosis (MS), but clinical data on oxidative stress markers in MS patients were inconsistent. This study sought to quantitatively summarize the data of oxidative stress markers in the blood and cerebrospinal fluid (CSF) of patients with MS in the literature. We conducted a systematic search of PubMed and Web of Science and included studies if they provided data on the concentrations of oxidative stress markers in the peripheral blood and CSF of MS patients and healthy control (HC) subjects. The systematic search resulted in inclusion of 33 studies with 2407 MS patients and 2258 HC subjects for meta-analysis. Random effects meta-analysis demonstrated that patients with MS had significantly increased concentrations of blood oxidative stress markers compared with HC subjects for malondialdehyde (MDA; Hedges'g, 2.252; 95% CI,1.080 to 3.424; p < 0.001) and lipid hydroperoxide by tert-butyl hydroperoxide-initiated chemiluminescence (CL-LOOH; Hedges'g, 0.383; 95% CI,0.065 to 0.702; p = 0.018). In contrast, concentrations of albumin (Hedges'g, -1.036; CI,-1.679 to -0.394; p = 0.002) were significantly decreased in MS patients when compared with HC subjects. However, the other analyzed blood oxidative stress markers did not show significant differences between cases and controls. Furthermore, this meta-analysis showed significant association between CSF MDA and MS (Hedges'g, 3.275; 95% CI, 0.859 to 5.691; p = 0.008). Taken together, our results revealed increased blood and CSF MDA, and decreased blood albumin levels in patients with MS, strengthening the clinical evidence of increased oxidative stress in MS.